Newborn screening for congenital adrenal hyperplasia in New York State - Melissa Pearce; Lenore DeMartino; Rebecca McMahon; Rhonda Hamel; Breanne Maloney; Daniele-Marisa Stansfield; Emily C. McGrath; Amanda Occhionero; Adam Gearhart; Michele Caggana; Norma P. Tavakoli (Molecular Genetics and Metabolism Reports, 2016)
From 2007 to 2014 the New York State (NYS) Newborn Screening (NBS) program screened 2 million newborns for congenital adrenal hyperplasia (CAH). The data was analyzed to determine factors that affect 17α-hydroxyprogesterone levels and assist in developing algorithm changes that would improve the positive predictive value of the methodology being used. The concentration of 17-OHP in dried blood spots was measured using the AutoDELFIA Neonatal 17-OHP kit (Perkin Elmer, Turku, Finland). During the 8 year period of this study 2476 babies were referred, 105 babies were diagnosed with CAH (90 with the salt-wasting (SW), 8 with simple virilizing (SV), 5 with non-classical CAH, and 2 with another enzyme deficiency) and, 14 with possible CAH. Three false negative cases with SV-CAH were reported to the program. Of the total 108 known cases, 74 (69%) infants were detected by newborn screening in the absence of clinical information, or, known family history. The incidence of CAH in NYS is 1 in 18,170 with a ratio of SW to SV of 8.2:1. The incidence of CAH is lower in Black infants than in White, Hispanic and Asian infants. Despite a lower mean birth weight, female infants have a lower mean 17-OHP value than male infants and are under-represented in the referred category. As per other NBS programs the false positive rate is exacerbated by prematurity/low birth weight and by over-early specimen collection.